2016
DOI: 10.1007/s11940-016-0431-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Childhood Migraine

Abstract: While the diagnosis of migraine in children is generally straightforward, treatment can seem complex with a number of medication choices, many of which are used "off label." Patients with intermittent migraines can often be managed with ibuprofen or naproxen taken as needed. Unfortunately, by the time that children present to our practice, they have often tried these medications without improvement. Triptans are frequently prescribed to these patients with good success. It is important to make the patient awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Data for propranolol, atenolol, and carvedilol in children is primarily available for varying indications such as portal hypertension, congestive heart failure, migraines, and arrhythmias, suggesting efficacy with an acceptable safety profile [110][111][112][113]. Minimal studies, however, have examined their use in HTN.…”
Section: Beta Blockers Efficacymentioning
confidence: 99%
“…Data for propranolol, atenolol, and carvedilol in children is primarily available for varying indications such as portal hypertension, congestive heart failure, migraines, and arrhythmias, suggesting efficacy with an acceptable safety profile [110][111][112][113]. Minimal studies, however, have examined their use in HTN.…”
Section: Beta Blockers Efficacymentioning
confidence: 99%
“…Literature survey of TDL and VPL revealed that several analytical techniques were employed such as high-performance thin layer chromatography (HPTLC) [7], high-performance liquid chromatography (HPLC) [8-12] and LC-MS/MS [13,14]. Aim of the present work was to develop an improved, accurate and rapid LC-MS/MS technique with low retention time.…”
Section: Fig 2: Structure Of Verapamilmentioning
confidence: 99%
“…In addition, these headaches have a severe impact on different aspects of quality of life of children and their families. Therefore, effective management of these headaches is required [1][2][3].…”
Section: Introductionmentioning
confidence: 99%